Analysis of Mathematical Ability of Matrix Multiplication of Class Xl Students - Linda Purwanti; Mailatul muyassaroh (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to analyze the mathematical abilities of class XI students in matrix multiplication. The research method used is survey research using a special test designed to measure students' matrix multiplication abilities. Data was collected from class XI students through tests covering various aspects of matrix multiplication. Analysis was carried out to evaluate the level of students' mathematical abilities in the context of matrix multiplication and the factors that influence it. The results of the research will provide insight into students' level of understanding of the concept of matrix multiplication and can be used as a basis for developing more effective learning strategies.